IMPROVING INDONESIAN EFL LEARNERS’ PRONUNCIATION THROUGH AUDIOLINGUAL METHOD PRINCIPLES - Pariyanto Pariyanto (Pusat Pengembangan Bahasa IAIN Tulungagung, 2012)
This paper puts forward the way to improve Indonesian EFL learners’ pronunciation through Audiolingual Method principles. It will look at the critical period hypothesis, where the notion of ‘native-like accent can be achieved’ refers to. The Audiolingual Method, which emphasizes the teaching of spoken language and sees the language as a matter of habit will be used as a basis to teaching EFL learners’ pronunciation. Both Indonesian and English segmental features will be discussed and compared in which the pronunciation teaching can be effectively delivered by identifying the difference between the two languages. In addition, the technology-assisted pronunciation teaching is presented as tools for helping EFL teachers in conveying a pronunciation course.